In Vitro Antibacterial Potential of Extracts of Sterculia africana, Acacia sieberiana, and Cassia abbreviata ssp. abbreviata Used by Yellow Baboons (Papio cynocephalus) for Possible Self-Medication in Mikumi National Park, Tanzania - Kirabo, Irene; Mabiki, Faith P.; Mdegela, Robinson H.; Obbo, Christopher J. D. (International Journal of Zoology, 2018)
In the animals in general and nonhuman primates in particular self-medication has been widely reported; however, little is still known about the pharmacological activity of the extracts present in their daily diet. The in vitro antibacterial activity of the stem, root bark, and leaf extracts of three selected plants on which yellow baboons feed in an unusual manner in Mikumi National Park, Tanzania, was evaluated. Crude plant extracts were tested against Gram positive and Gram negative bacteria of medical and veterinary importance employing a modified agar well diffusion method and Minimum Inhibitory Concentration (MIC) technique. The lowest MIC value for Gram positive strains was 0.31 mg/ml demonstrated by Cassia abbreviata ssp. abbreviata against Staphylococcus aureus (ATCC 25923). The highest susceptibility to the ethanol plant extracts was exhibited by Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus, examples of microbes that affect both human and nonhuman primates. These findings demonstrate that the plant extracts from Sterculia africana, Acacia sieberiana, and Cassia abbreviata ssp. abbreviata have antibacterial activity and may be used as feed for their prophylactic benefits. Remarkably, the lowest MIC of 0.16 mg/ml was only 16-fold weaker than Gentamicin, a standard drug.